Clostridium difficile Problematik Infeksi Clostridium difficile: Infeksi C. difficile - Tjampakasari, Conny Riana; Hanayurianingtyas, Deajeng Laras (Fakultas Kedokteran Universitas Trisakti, 2023)
Clostridium difficile is a Gram-positive, strictly anaerobic, spore-forming bacterium. The virulence factor of this bacterium is the toxins it produces, namely enterotoxin A (TcdA ) and cytotoxin B (TcdB). Transmission occurs fecally orally by ingesting the spores of this bacteria. Clostridium difficile is the most common cause of fulminant-associated in hospitals and other healthcare facilities and is of significant concern because of the increasing morbidity and mortality rates as well as increased healthcare costs. Elderly patients or patients with compromised immune systems are patients at the highest risk for this case. Clostridiosis present a varied spectrum of infection, ranging from self-limited diarrhea, mild to moderate diarrhea, to serious diarrhea, pseudomembranous colitis, and life-threatening fulminant colitis which can be life-threatening and can cause death. The diagnosis is made by direct detection of Clostridium difficile toxin in the feces. Although empiric therapy known as vancomycin and fidaxomycin have been used as the antibiotic choice, prompt identification of patients with symptoms of Clostridium difficile infection is very important because most patients respond quickly to antimicrobial therapy. may result in death. Prompt identification of patients with symptomatic Clostridium difficile infection is essential as the majority of patients respond quickly to antimicrobial therapy. Prevention is best achieved by implementing infection control measures and appropriate use of antimicrobial agents. Health professional education regarding preventive measures such as hand washing, wearing gloves, decontamination of medical equipment, and the proper environment is highly recommended.